(3WhGdY GdCfhGQ dTQM GdOQ GdeNJGQs - (3eMeO YGHO GdSfOj , eMeO YGHO Hf CMeO Hf Ydj Hf jYbhH GdSfOj GdCfUGQj,J (B1257 (3g` s ((3Ydi Ydi MSf GdTQbGhi GdMdhGfi s)
(3ChdgG (B:s
(3jHOC HcJGH GdML s
(3BNQgG (B:s
(3jfJgi HHGH GdgOi s
(3GdfSNI HgG MhGTs
(3HgG fXGe G dJYbjHIs
(3HChdgG agQSJ ddeNWhWs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfajs